Collaborative environmental governance frameworks a practical guide - Gieseke, Timothy M. (Boca Raton CRC Press, 2020)
"This book takes a practical approach to understanding and describing collaborative governance for resolving environmental problems. It introduces a new collaborative governance assessment model and recognizes that collaborations are a natural result of organizations converging around complex issues. Rather than identifying actors by their type of organization, the actors are identified by the type of role they play. This approach is aligned with how individuals and organizations interact in practice, and their dependance on collaborations to solve emerging environmental problems. The book discusses real cases with governance issues and creates new frameworks for collaborations"--
Introduction -- Section One: Something Special is Happening -- Entering a Collaborative Era -- Collaborations as a Hybrid Organization -- Preparing to Collaborate -- Section Two: The Science of Collaborative Governance -- Of Actors and Styles -- What Style of Governance do you 'Swim In'? -- Governance Footprints and Frameworks -- Section Three: Social Complexity and Three Wicked Case Studies -- Social Complexity -- The Nature of Societal Problems -- The Nature of Three Wicked Case Studies -- Section Four: Designing Collaborative Governance Frameworks -- A Meta-Governor's Roles in Three Wicked Case Studies -- Making Collaborative Governance Happen -- Conclusion
Includes bibliographical references.
Keywords: Environmental management; Organizational effectiveness; Communication in organizations